Evaluating the Effectiveness of Legal Frameworks in Promoting Integrity and Preventing Maladministration in Public Agencies in Jambi Province - Nova Elsyra; Syahwami; Joko Sunaryo; Burhanuddin; Hamirul (Enigma in Law, 2025)
Promoting public sector integrity and preventing maladministration are crucial for good governance and public trust. Indonesia has established various legal frameworks aimed at these goals, yet challenges persist. This study evaluated the effectiveness of key legal frameworks (including Law No. 30/2014 on Government Administration, Law No. 5/2014 on State Civil Apparatus, Law No. 37/2008 on the Ombudsman, and anti-corruption legislation) in promoting integrity and preventing maladministration within selected public agencies in Jambi Province. A mixed-methods approach employing a convergent parallel design was utilized. Data collection occurred between June and September 2024. Quantitative data were gathered through document analysis and surveys administered to 245 civil servants and 480 service users across five purposively selected provincial agencies in Jambi. Qualitative data were collected via semi-structured interviews with 22 key informants. Data were generated based on regional trends and literature. Quantitative data were analyzed using descriptive statistics and ANOVA, while qualitative data underwent thematic analysis. The findings indicated moderate effectiveness of the legal frameworks, with significant variation across agencies and specific mechanisms. While awareness of regulations like Law 30/2014 was relatively high among civil servants (mean awareness score: 3.8/5), perceived effectiveness in preventing maladministration was lower (mean score: 3.1/5). Integrity Zone initiatives showed a positive but limited impact. Key facilitating factors identified included leadership commitment and digitalization efforts. Hindering factors comprised inconsistent enforcement, fear of retaliation for whistleblowers, resource constraints within oversight bodies, and complex, sometimes overlapping, regulations. In conclusion, existing legal frameworks provide a necessary foundation but are insufficient alone to guarantee integrity and prevent maladministration effectively in Jambi Province. Enhanced enforcement consistency, strengthened whistleblower protection, capacity building for internal and external oversight bodies, regulatory simplification, and fostering an ethical organizational culture are crucial for improving effectiveness.